2020
DOI: 10.1093/biomet/asaa038
|View full text |Cite
|
Sign up to set email alerts
|

Regression-adjusted average treatment effect estimates in stratified randomized experiments

Abstract: Summary Linear regression is often used in the analysis of randomized experiments to improve treatment effect estimation by adjusting for imbalances of covariates in the treatment and control groups. This article proposes a randomization-based inference framework for regression adjustment in stratified randomized experiments. We re-establish, under mild conditions, the finite-population central limit theorem for a stratified experiment, and we prove that both the stratified difference-in-means e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
66
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(68 citation statements)
references
References 18 publications
2
66
0
Order By: Relevance
“…Although the Wald estimator exhibits good asymptotic properties, it does not use covariate information. If these baseline covariates can predict the potential outcomes, covariate adjustment tends to reduce the variance of the estimated treatment effect (Lin, 2013;Bloniarz et al, 2016;Fogarty, 2018;Yue et al, 2019;Liu and Yang, 2020;Li and Ding, 2020). In this section, we propose three model-assisted CATE estimators and study their asymptotic properties under the finite-population and randomization-based inference framework.…”
Section: Model-assisted Cate Estimatorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the Wald estimator exhibits good asymptotic properties, it does not use covariate information. If these baseline covariates can predict the potential outcomes, covariate adjustment tends to reduce the variance of the estimated treatment effect (Lin, 2013;Bloniarz et al, 2016;Fogarty, 2018;Yue et al, 2019;Liu and Yang, 2020;Li and Ding, 2020). In this section, we propose three model-assisted CATE estimators and study their asymptotic properties under the finite-population and randomization-based inference framework.…”
Section: Model-assisted Cate Estimatorsmentioning
confidence: 99%
“…In randomized experiments with perfect compliance, researchers have proposed regression adjustment methods with treatment assignment by covariate interactions to estimate the average treatment effect, and showed that the resulting estimator is generally more efficient than the simple difference-in-means estimator (Lin, 2013;Bloniarz et al, 2016;Fogarty, 2018;Yue et al, 2019;Liu and Yang, 2020;Li and Ding, 2020). Motivated by these ideas and considering non-compliance, we propose an indirect least squares (ILS) method that includes the treatment assignment by covariate interactions in the two linear (working) models.…”
Section: Introductionmentioning
confidence: 99%
“…The robustness test of DID ensures that all effects are indeed caused by the implementation of the policy [ 18 20 ]. Besides, the effect is mainly manifested in the following two aspects.…”
Section: Research Model On the Impact Of Utcp On Female Employmentmentioning
confidence: 99%
“…In particular, Theorem 3.3 gives the asymptotic distribution of our regression adjusted rank-based estimator. Previously, the asymptotic distributions of regression adjusted difference-inmeans type estimators were derived under different randomization strategies (Fogarty, 2018;Li and Ding, 2020;Liu and Yang, 2020;Su and Ding, 2021;Zhao and Ding, 2021b). These results build on the results of Li and Ding (2017) and do not apply to rank-based estimators, as already discussed above.…”
Section: Summary Of Our Contributionsmentioning
confidence: 99%
“…Lin (2013) proposed a regression adjusted estimator by modifying the ANCOVA model to include the interactions of the treatment and covariates that is asymptotically at least as efficient as the unadjusted difference-in-means estimator. Recently, regression adjusted or model assisted estimators have been developed for different study designs (Fogarty, 2018;Li and Ding, 2020;Liu and Yang, 2020;Su and Ding, 2021;Zhao and Ding, 2021b). But, these regression adjustment methods based on linear models which typically use robust standard errors from the classical literature (Huber, 1967;White, 1980) are still sensitive to heavy-tailed distributions, extreme values or outliers in the potential outcomes (MacKinnon and White, 1985;Young, 2018).…”
Section: Introductionmentioning
confidence: 99%